2017
DOI: 10.1016/j.molcel.2016.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Cas9 Enhance the Rate of Acquisition of Viral Spacer Sequences during the CRISPR-Cas Immune Response

Abstract: SUMMARY Clustered regularly interspaced short palindromic repeat (CRISPR) loci and their associated (Cas) proteins encode a prokaryotic immune system that protects against viruses and plasmids. Upon infection, a low fraction of cells acquire short DNA sequences from the invader. These sequences (spacers) are integrated in between the repeats of the CRISPR locus and immunize the host against the matching invader. Spacers specify the targets of the CRISPR immune response through transcription into short RNA guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 29 publications
5
44
0
Order By: Relevance
“…Interestingly, a rapid increase in the spacer uptake rate increased the likelihood of spacers that self-target the bacterial host genome. This theoretical result agreed with an experiment in which an engineered Cas9 in S. pyogenes led to increased spacer acquisition but also increased autoimmunity [66]. That is, even assuming a constant CRISPR array length, an increased rate of acquisition meant a single bacterium would incorporate a greater number of spacers, and so there was a greater cumulative probability that one of those spacers would activate an autoimmune response.…”
Section: Effects Of Spacer Acquisition and Deletion Ratessupporting
confidence: 85%
“…Interestingly, a rapid increase in the spacer uptake rate increased the likelihood of spacers that self-target the bacterial host genome. This theoretical result agreed with an experiment in which an engineered Cas9 in S. pyogenes led to increased spacer acquisition but also increased autoimmunity [66]. That is, even assuming a constant CRISPR array length, an increased rate of acquisition meant a single bacterium would incorporate a greater number of spacers, and so there was a greater cumulative probability that one of those spacers would activate an autoimmune response.…”
Section: Effects Of Spacer Acquisition and Deletion Ratessupporting
confidence: 85%
“…We next replaced the fNM4g4-targeting CRISPR array with a single repeat in order to test the effects of trL::Tn on a 'naïve' CRISPR system with no immunological history. In liquid and semi-solid phage immunity assays, we found that trL::Tn enhances CRISPR immunity by roughly 100-fold, similar to a previously identified mutation in cas9 (hcas9) 47 that boosts spacer acquisition rates ( Fig. 1C-D, S2B).…”
Section: Tn-seq Reveals a Tracrrna Mutant With Enhanced Crispr Immunitysupporting
confidence: 80%
“…In many cases where the regulatory mechanisms are known, host-encoded transcription factors interact with CRISPR-Cas promoters 32,33,35,36 , although several studies have shown that archaeal type I-A systems can be intrinsically controlled by dedicated Cas-encoded transcription factors 25,[37][38][39][40] . Given that CRISPR systems are frequently horizontally transferred in the wild [41][42][43] , these intrinsic controllers could help prevent autoimmune toxicity [44][45][46][47] in a new host that has not had time to evolve its own regulatory strategy. However, few CRISPR loci -and no type II loci -encode dedicated transcription factors, and it is unclear whether alternative mechanisms of intrinsic regulation exist.…”
Section: Introductionmentioning
confidence: 99%
“…CRISPR–Cas9 is a leading family of Class 2 enzymes for mechanistic studies due to its widespread use in gene editing and cell-free DNA detection (DiCarlo et al, 2013; Ding et al, 2014; Han, Slivano, Christie, Cheng, & Miano, 2015; Heler et al, 2017; Jinek et al, 2014; Long et al, 2014; Niu et al, 2014; Sander & Joung, 2014; Shen et al, 2013; Strong & Musunuru, 2017; Wang et al, 2015; Zetsche et al, 2017). Cas9 may be further divided into three subtypes depending on the sequences of Cas9 and the association with proteins involved in spacer acquisition (Chylinski, Le Rhun, & Charpentier, 2013; Mir, Edraki, Lee, & Sontheimer, 2018; Shmakov et al, 2017).…”
Section: Introductionmentioning
confidence: 99%